2017
DOI: 10.1038/cddis.2017.473
|View full text |Cite
|
Sign up to set email alerts
|

Tat-protein disulfide-isomerase A3: a possible candidate for preventing ischemic damage in the spinal cord

Abstract: In the present study, we searched for possible candidates that can prevent ischemic damage in the rabbit spinal cord. For this study, we used two-dimensional gel electrophoresis followed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, in sham- and ischemia-operated animals. As the level of protein disulfide-isomerase A3 (PDIA3) significantly decreased 3 h after ischemia/reperfusion, we further investigated its possible role against ischemic damage using an in vitro spinal cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…In the present study, we focused upon the effects of exogenous PDIA3 on the proliferating cells and neuroblast numbers in the hippocampus, which is one of neurogenic regions in adult brain. First of all, we confirmed the efficient delivery of Tat-PDIA3 in the DG by immunohistochemistry for polyhistidine because we added polyhistidine tag in the Tat-PDIA3 vector as shown in the previous studies (Yoo et al, 2017(Yoo et al, , 2019. Tat-PDIA3-treated control and ischemic groups showed strong polyhistidine immunoreactivity in the DG, while vehicle-treated control and ischemic groups did not show any prominent polyhistidine immunoreactivity in the hippocampal DG.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the present study, we focused upon the effects of exogenous PDIA3 on the proliferating cells and neuroblast numbers in the hippocampus, which is one of neurogenic regions in adult brain. First of all, we confirmed the efficient delivery of Tat-PDIA3 in the DG by immunohistochemistry for polyhistidine because we added polyhistidine tag in the Tat-PDIA3 vector as shown in the previous studies (Yoo et al, 2017(Yoo et al, , 2019. Tat-PDIA3-treated control and ischemic groups showed strong polyhistidine immunoreactivity in the DG, while vehicle-treated control and ischemic groups did not show any prominent polyhistidine immunoreactivity in the hippocampal DG.…”
Section: Discussionsupporting
confidence: 78%
“…In previous studies, we generated Tat‐PDIA3 fusion protein and observed the intracellular delivery of Tat‐PDIA3 fusion protein (Yoo et al, , ) as well as the colocalization of PDIA3 with ER tracker (Yoo et al, ). In addition, we found the neuroprotective actions of Tat‐PDIA3 and its mechanisms in the gerbil brain ischemia (Yoo et al, ) and rabbit spinal cord ischemia (Yoo et al, ). Especially, administration of PDIA3 protected neurons from hydrogen peroxide‐induced oxidative stress in HT22 cells and ischemic damage in the gerbil hippocampal CA1 region (Yoo et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals (n = 20 in each group) were anesthetized with a mixture of alfaxalone and xylazine at 8 weeks after diet feeding and the hippocampus was isolated from the whole brain. Hippocampal tissues were suspended in a sample buffer [29], which consisted of 30 mM Tris, 7 M urea, 2 M thiourea, 65 mM dithiothreitol (DTT), 4% 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate (CHAPS) with 40 µL protease inhibitor (pH 8.5). Suspensions were sonicated five times for 10 sec and centrifuged at 45,000 rpm for 45 min.…”
Section: Protein Preparation For 2dementioning
confidence: 99%
“…The main advantage of 2DE is the capability of simultaneously resolving complex protein mixture, up to 10,000, allowing their quantitation as well as the analysis of all post-translational modifications [5]. 2DE has been adopted for a variety of applications: from drug discovery to diagnostics, therapy, and biochemistry [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%